Chemical characterization of biochar from sugarcane tips produced by hydrothermal carbonization and addition of organic catalysts - Pérez-Cabrera, Carlos Alberto; Juárez-López, Porfirio; Anzaldo-Hernández, José; Alia-Tejacal, Irán; Salcedo-Pérez, Eduardo; Guillén-Sánchez, Dagoberto; Balois-Morales, Rosendo; López-Martínez, Víctor; Castro-Brindis, Rogelio (REVISTA TERRA LATINOAMERICANA, 2021)
Biochar is a carbon-rich material obtained by thermochemical conversion produced from organic materials in an oxygen-limited environment, which can be used as a soil enhancer. The objective of the research was to evaluate the yield of converted biochar, nutrient concentration and structure of sugarcane tips biochar produced by hydrothermal carbonization and addition of organic catalysts. The experimental design was completely randomized with six replicates. Treatments were three catalysts: citric, maleic and propionic acid in 5 and 10% concentrations each, which were added during biochar production. The respective control was biochar without addition of any catalyst, for a total of seven treatments. The biomass to biochar conversion yield and the total nutrient concentration of N, P, Ca, Mg and Na were determined. The extractable concentration of the same nutrients except for Na was also determined, as well as the pH and the electrical conductivity and structure of the biochar. The highest yields of biochar made from sugarcane tips by hydrothermal carbonization were 37.8% with the addition of citric acid at 10% as catalyst, as well as 34.9 and 36.1% with the addition of maleic acid at 5 and 10%, respectively. In general, due to the total and extractable nutrient concentration of biochar, its electrical conductivity (0.30-0.46 dS m-1), as well as its microsphere structure, sugarcane tips biochar could act as a soil enhancer, especially in alkaline soils due to the acid pH of the biochar produced.